The Sound of Semana Santa: The Meaning of Music for the Religious Experience of Participants of the Processions during Semana Santa in Antigua, Guatemala - Lensink, Jip (Student Undergraduate Research E-journal!, 2017)
This anthropological research gives insight in the meaning of music for the religious experience of participants of the processions in Antigua, Guatemala. By placing the theories of lived religion, material religion and aesthetics at the central stage, the process whereby the marchas fúnebres, the music played in the processions, mediate religious experience for the participants is explained. The material-sensorial elements of the processions, the practice of carrying, and the emotional effect of the music which refers to extra-musical memories, all provide the context for and strengthen the communication of the participants with God.